Analisis Keberhasilan Implementasi Smart Governance dalam Mendukung Pembangunan Smart City di Indonesia - Gita Evellinda, Rahma Audyna; Indonesia (Journal of Governance Innovation, 2024)
The smart city concept arose as a solution to urban challenges, aiming to enhance the efficacy and efficiency of urban planning. The smart city concept aims to address issues such as delayed public services, inflexible service procedures, and inefficiency through the use of smart governance. This study examines the implementation of smart cities in the context of smart governance in Indonesia. Its objective is to determine the level of smart governance implementation in Indonesia and its implications for supporting smart cities in the country. The research employed a descriptive qualitative methodology. The research employs a data gathering method that relies on secondary sources, including scholarly journals and online mass media, spanning from 2017 to 2024. This time frame aligns with the research focus on smart governance in Indonesia. The news sources utilized consisted of six major mass media outlets, with a news coverage level of 59 units of news intensity. The data analysis employed a three-stage process, consisting of data reduction, data display, and generating conclusions. This study employs Qualitative Data Analysis Software (QDAS) utilizing the Nvivo 12 plus tools. This study use data source triangulation methods to acquire systematic, factual, and precise data. The findings of this study indicate that the implementation of smart governance in Indonesia's smart city initiatives has not been entirely successful. The indicators of smart governance implementation have not been fully met, and there are still unresolved issues that require correction and improvement.